Arbitrary Nondemolition Measurements through Hamiltonian Stabilization for Quantum Error Correction - Rodrigo G. Cortiñas (PRX Quantum)
Quantum measurement is performed by coupling a quantity A[over ^] of a system to a “meter” and reading the meter. In the regime of strong measurement, the possible outcomes and the final state are entirely defined by A[over ^], with probabilities dictated by the initial state. In this work, we will be interested in the regime in which a strong self-Hamiltonian, and not the coupling, defines the measurement outcomes and the final state. In this regime, the expectation value of any arbitrary set of observables can be measured in a quantum nondemolition (QND) way without reset or repreparation of the state. We discuss applications that include single-shot measurement of the expectation value of all noncommuting observables from a single copy of the state, without any statistics or ensembles, and the decoding of dephasing errors in a Schrödinger-cat qubit quantum error-correction (QEC) code. In the latter, the error syndrome is obtained from single-shot QND measurements of the mean photon number of the cat, even if neither the cat code words nor the stabilizing Hamiltonian commute with the photon-number operator.